Plant-based Functional Foods from South Asia – Importance and Requirement for Better Healthcare: A review - Tiwari, Prabesh; Bhusal, Ishwar; K.C., Bishnu Maya; Lamichhane, Janardan (Journal of Nepal Biotechnology Association, 2026)
Functional foods incorporating plant-derived bioactive compounds offer potential health benefits by providing nutrition in the form of polyphenols, dietary fiber, and vitamins. South Asia is rich in biodiversity and ethnobotanical heritage, and has the potential to provide a wide range of plants with high nutritional value. The existing knowledge and utilization of plants from South Asia that have been incorporated into functional food formulations, with specific emphasis on Nepal, is very limited. Cereals, millets, fruits, and medicinal plants have long been used in households to treat various health conditions, but their rich phytochemical and dietary fiber content remains incompletely understood. Plants such as Moringa, Ginger, and Amla have been successfully incorporated into bakery products, gummies, beverages, and dairy products. Additionally, several underutilized plants in Nepal and the region show potential for future use in functional food development. This review highlights the potential of plants in South Asia and functional food formulations based on these plants.